Government Expenditure and Economic Growth in Vietnam: Does Public Investment Matter in The Long-Term? - Hoa Thi Nguyen (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study focuses on the correlation between public investment, current expenditure and payment for government debt, and economic growth in short-run and long-run estimations.Design/Methodology/Approach: Macro data of Vietnam in the period 1991-2020 were extracted from the World Bank and the Vietnam General Statistics Office. This research employed the Autoregressive Distributed Lag (ARDL) for time series.Research findings: The results of this study uncovered that an improvement in public investment could enhance economic growth; it is also true of the government’s current spending. However, it is worth noting that the coefficients of changes in public investment and government current spending reduced the economic growth change in one and two periods ago. Moreover, debt payment was found to have a negative effect on the economy at all lags with different levels of significance.Theoretical contribution/Originality: This study provides empirical evidence on the role of government spending in economic growth, thereby confirming that Keynesian theory still holds in the case of Vietnam. The study also verifies the vital role of government activity in regulating economic development through investment and expenditure.Practitioner/Policy implication: Some important implications for policymakers focusing on government spending are: (i) The government needs to have an investment strategy that focuses on the important areas, such as infrastructure and technology foundation. (ii) Government needs to improve accountability and transparency in the management. (iii) Supportive policies on capital, technology, human resources, and the market must be continued to encourage economic investment activities. (iv) The selection, evaluation, and approval of investment portfolios should be carefully and appropriately made.Research limitation: This study was limited by looking at the overview of government spending with economic growth, ignoring the spending structure due to the lack of necessary data. Therefore, the following studies need to clarify the spending structure of Vietnam to determine which expenditure types have negative/positive impacts on economic growth, thereby providing incentive solutions and necessary support from the government.